2010
DOI: 10.1097/iae.0b013e3181f57d58
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab During Pregnancy

Abstract: Offering pregnant patients intravitreal bevacizumab therapy during pregnancy for off-label ocular indications can result in significant visual improvement. No adverse events related to treatment occurred in any patient included in this study. Additional studies with more patients and longer follow-up duration are required to identify any risks associated with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 35 publications
(32 reference statements)
1
41
0
2
Order By: Relevance
“…7 The other reports showed that patients delivered healthy full-term infants with no documented adverse events related to treatment, and no cases of pregnancy complication in 2 cases of CNV of an origin other than age-related macular degeneration, and in one case of PM-related CNV, respectively. 8,9 Our experience confirms the preliminary results of the previous case reports, reporting an uneventful pre-and postnatal course in a highly myopic woman and her baby. After treatment, visual acuity had favorably improved, with longterm stabilization.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…7 The other reports showed that patients delivered healthy full-term infants with no documented adverse events related to treatment, and no cases of pregnancy complication in 2 cases of CNV of an origin other than age-related macular degeneration, and in one case of PM-related CNV, respectively. 8,9 Our experience confirms the preliminary results of the previous case reports, reporting an uneventful pre-and postnatal course in a highly myopic woman and her baby. After treatment, visual acuity had favorably improved, with longterm stabilization.…”
Section: Discussionsupporting
confidence: 94%
“…5 Our knowledge regarding fetus exposure to bevacizumab is based on preclinical studies and limited clinical experience. [6][7][8][9] Preclinical studies in rabbits showed teratogenic effects and an increased number of miscarriages after being intravenously administered bevacizumab. 10 In our case, the patient was administered an intravitreal bevacizumab injection during the first trimester of pregnancy, more specifically at 7 weeks and 3 days of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Für die Verwendung dieser Substanzen in der Schwangerschaft existieren keine Stu dien, sondern lediglich Einzelfallberichte. Es wird sowohl über unkomplizierte Schwangerschaftsverläufe berichtet als auch über Aborte [19,26,30]. Wir selber haben 2 unauffällige Schwangerschaften unter der Therapie mit Bevacizumab be obachtet.…”
Section: Vegf-inhibitorenunclassified
“…However, the use of intravitreal bevacizumab injection (IVB) is gaining wide acceptance as an off-label therapy for a disease that may affect women of childbearing age, as choroidal neovascularization from etiologies other than age-related macular degeneration [1], cystoid macular edema associated with uveitis [1], and diabetic retinopathy [1], particularly diabetic macular edema.…”
mentioning
confidence: 99%
“…Bevacizumab is a full-length humanized monoclonal antibody that binds all vascular endothelial growth factor splice variants [1]. Preclinical studies in rabbits showed teratogenic effects and an increased number of miscarriages after intravenous administration of bevacizumab [2].…”
mentioning
confidence: 99%